GUIDELINES FOR THE DEVELOPMENT OF EAR TRAINING TEACHING AND LEARNING OF PRE-COLLEGE STUDENTS, COLLEGE OF MUSIC, MAHIDOL UNIVERSITY - Jumneanpan, Wipawan (Journal of Buddhist Education and Research (JBER), 2024)
The objective of this research is to study: 1) ear training teaching and learning approaches in the pre-college level, College of Music, Mahidol University; and 2) guidelines to develop ear training teaching and learning methods for the pre-college level, College of Music, Mahidol University. The research was conducted using focus group discussion, non-participant observation, and semi-structured interview. Respondents were divided into two groups: Group 1 consisting of 36 students in Mathayom 4-6 (higher secondary level), Pre-College, College of Music, Mahidol University; and Group 2 consisting of 12 Pre-College committee members, ear training instructors, and music educators, all from purposive sampling. Research instruments included forms for focus group discussion, non-participant observation, and semi-structured interview. Research findings were separated into two parts. First, teaching and learning approaches were assessed in five aspects: 1) The first part of the curriculum and content of Mathayom 4 overlapped with TIME’s Grade 9 aural skills and students in Mathayom 5 and 6 were grouped based on their ability; 2) The instructors were well-prepared and utilized good teaching techniques; 3) Learning activities were consistent and diverse; 4) The media and equipment were modern and suitable for the content and the classrooms were appropriate; and 5) The evaluation and assessment was clear and based on various skills. Second, the guidelines to develop ear training teaching and learning highlighted five aspects: 1) Curriculum and Content; 2) Instructors; 3) Learning Activities; 4) Media, Equipment and Classroom; and 5) Evaluation and Assessment.